The Pandemic’s Shadow: Measles Vaccination Challenges and Trends - Ilango, Malar (Indian Journal of Community Health, 2024)
Measles is a highly contagious, serious disease caused by a virus. Before the introduction of measles vaccine in 1963, major epidemics occurred approximately every 2-3 years and caused an estimated 2.6 million deaths each year (1). Government of India launched Universal Immunization Program in 1985, which provides vaccination against 8 life threatening disease including measles and 65% vaccine coverage was achieved. In order to increase the vaccination coverage, Mission Indradhanush was launched in phased manner which aimed to fully immunize more than 90% of newborn by 2020. India has adopted the National strategic Plan for achieving and sustaining measles and Rubella elimination in India and has vaccinated over 324 million children between 2017 and 2020 through MR vaccination campaign (2). Due to the lag, India had shifted its self-imposed deadline to eliminate measles to 2023 and launched another vaccination campaign in 2021 called the Intensified Mission Indradhanush 3.0, targeting unvaccinated children.